2016
DOI: 10.1016/j.copbio.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization and dynamics of polymeric cell culture substrates

Abstract: The promise of growing tissues to replace or improve the function of failing ones, a practice often referred to as regenerative medicine, has been driven in recent years by the development of stem cells and cell lines. Stem cells are typically cultured outside the body to increase cell number or differentiate the cells into mature cell types. In order to maximize the regenerative potential of these cells, there is a need to understand cell-material interactions that direct cell behavior and cell-material dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…We are particularly interested in utilizing these thiol-ene materials downstream as functional biological scaffolds, as the unreacted thiols can be used for downstream surface functionalization. [32][33][34] Providing threshold functionality by means of the radical-trapping inhibitor TEMPO points toward a general approach for formulating VAM-compatible materials, whether oxygen-inhibited or not. The sharpness of the threshold and its interplay with printing resolution and part mechanical properties warrant further investigation.…”
Section: Mechanical Testing Of Bulk Samples Revealed That Samplesmentioning
confidence: 99%
“…We are particularly interested in utilizing these thiol-ene materials downstream as functional biological scaffolds, as the unreacted thiols can be used for downstream surface functionalization. [32][33][34] Providing threshold functionality by means of the radical-trapping inhibitor TEMPO points toward a general approach for formulating VAM-compatible materials, whether oxygen-inhibited or not. The sharpness of the threshold and its interplay with printing resolution and part mechanical properties warrant further investigation.…”
Section: Mechanical Testing Of Bulk Samples Revealed That Samplesmentioning
confidence: 99%
“…In this respect, control over possible interactions between (electrospun) scaffolds and biomolecules or cells in general is of fundamental interest. Hence, various strategies to surface‐functionalize scaffolds with biologically active compounds such as RGD peptides, growth factors, or proteins have been studied to promote directed and non‐directed cell adhesion . Besides the possibility to display bioactive molecules on the scaffolds, a covalent chemical bond between the functionalizing entity and the scaffold is particularly useful to immobilize the active component on the scaffold surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, various strategies to surface-functionalize scaffolds with biologically active compounds such as RGD peptides, growth factors, or proteins have been studied to promote directed and non-directed cell adhesion. [3][4][5][6] Besides the possibility to display bioactive molecules on the scaffolds, a covalent chemical bond between the functionalizing entity and the scaffold is particularly useful to immobilize the active component on the scaffold surface. Poly(para-dioxanone) (PPDO) is wellknown as a suture in clinical use; however, it has not achieved a breakthrough in tissue engineering despite studies on tendon, bone, and Karola Luetzow and Paul J. Hommes-Schattmann contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical functionalization and physical adsorption of ECM proteins (such as collagen, fibronectin (FN), and laminin) are parts of a widespread strategy that can promote cell-SyP matrix interactions. [21][22][23][24][25] For instance, Zahari et al 26 produced electrospun cell scaffolds from PMMA containing physically adsorbed collagen type 1 or laminin for muscle-tissue regeneration. The authors found that the use of genipin as the crosslinking agent Fig.…”
Section: Syps Functionalization To Promote Cell Attachment and Proliferationmentioning
confidence: 99%